So how did Jehoiakim die? - Smit, E. J. (Journal for semitics, 1994)
The article explores the information about the death of king Jehoiakim in three different sources, namely the books of Kings, Chronicles and Jeremiah. It seems that the writer of Kings has no real interest in descriptionbing the death of Jehoiakim, his attention being focused on Jehoiakim's successor, Jehoiachin. The writer of Chronicles in his descriptionption hurries over these historical events to emphasize the doom of Jerusalem and of the land; although the last kings of Judah vanished from the scene there still was a future for the people. It seems that the most historically reliable information about the death of Jehoiakim is to be found in the prophecies of Jeremiah, although it is embedded in the categories and style of Jeremiah's prophetic utterances. It seems that Jehoiakim died a violent death, and had no burial whatsoever. The article concludes with the remark that the information in each of these sources must be read within the wider aims of each separate book.